Biological X-ray irradiator characterization for use with small animals and cells - Bruno, A. Colello (Braz J Med Biol Res, 2017)
This study presents the characterization of an X-ray irradiator through dosimetric tests, which confirms the actual dose rate that small animals and cells will be exposed to during radiobiological experiments. We evaluated the linearity, consistency, repeatability, and dose distribution in the positions in which the animals or cells are placed during irradiation. In addition, we evaluated the performance of the X-ray tube (voltage and tube operating current), the radiometric survey (leakage radiation) and safety devices. The irradiator default setting was established as 160 kV and 25 mA. Tests showed that the dose rate was linear overtime (R(2)=1) and remained stable for long (constant) and short (repeatability) intervals between readings. The mean dose rate inside the animal cages was 1.27±0.06 Gy/min with a uniform beam of 95.40% (above the minimum threshold guaranteed by the manufacturer). The mean dose rate inside the cell plates was 0.92±0.19 Gy/min. The dose rate dependence with tube voltage and current presented a quadratic and linear relationship, respectively. There was no observed mechanical failure during evaluation of the irradiator safety devices and the radiometric survey obtained a maximum ambient equivalent dose rate of 0.26 mSv/h, which exempts it from the radiological protection requirements of the International Atomic Energy Agency. The irradiator characterization enables us to perform radiobiological experiments, and assists or even replaces traditional therapy equipment (e.g., linear accelerators) for cells and small animal irradiation, especially in early research stages.